2007
DOI: 10.1073/pnas.0611513104
|View full text |Cite
|
Sign up to set email alerts
|

Properties of glutamate receptors of Alzheimer's disease brain transplanted to frog oocytes

Abstract: It is known that Alzheimer's disease (AD) is a synaptic disease that involves various neurotransmitter systems, particularly those where synaptic transmission is mediated by acetylcholine or glutamate (Glu). Nevertheless, very little is known about the properties of neurotransmitter receptors of the AD human brain. We have shown previously that cell membranes, carrying neurotransmitter receptors from the human postmortem brain, can be transplanted to frog oocytes, and their receptors will still be functional. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
29
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 34 publications
(24 reference statements)
6
29
0
Order By: Relevance
“…The microtransplantation method is very convenient for pharmacological and biophysical experiments of human native receptors. However, previous reports mention a large variability in the amplitude of responses among microtransplanted oocytes (10,11,19). Therefore, we determined the response distribution of single brains (SI Results and Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The microtransplantation method is very convenient for pharmacological and biophysical experiments of human native receptors. However, previous reports mention a large variability in the amplitude of responses among microtransplanted oocytes (10,11,19). Therefore, we determined the response distribution of single brains (SI Results and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lower levels of GABA A Rsubunits α1, α2, α4, δ, and β2 mRNAs in the prefrontal cortex of AD brains (3) and of α1, α5, and β3 mRNAs in the AD hippocampus (2,9) suggest that some receptors may have an altered functional profile in AD. Our initial experiments, evaluating the feasibility of recording the activity of native receptors from frozen brains (10) and of studying glutamate receptors in AD (11), revealed an unexpected and substantial decrease in the amplitude of ionic responses to GABA (i.e., GABA currents) in temporal cortices of AD brains. This reduction was correlated with diminished expression of all GABA transcripts analyzed (α1, α2, α5, β2, β3, γ2) and with decreased α1 subunit protein (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, fresh human brain tissues are difficult to obtain, and it was highly desirable to determine whether the frozen postmortem brain tissues that are available from brain banks all over the world could be used to study the function and structure of neurotransmitter receptors and ion channels of the human brain. Initial experiments using tissues from postmortem Alzheimer's brains have already shown that their cell membranes contain functional GABA and glutamate receptors as well as calcium channels (21,22). However, the postmortem intervals (PMIs) of the brains used in those studies were mostly only a few hours in duration (Ͻ5.3 h).…”
mentioning
confidence: 99%
“…Alteration in the composition, number, subtypes and/or activity of glutamate receptors have also been shown to be associated with mental illnesses, neurodegenerative diseases such as Alzheimer's and in other neurological disorders, such as epilepsy and ischemia (Meldrum 2000;Bernareggi et al 2006;Borbely et al 2009). Glutamate receptors are divided into two major groups based on the pathway that is activated upon binding of glutamate or other agonists to the receptors (Dingledine et al 1999).…”
Section: Glutamate Receptors: Physiological and Pathological Importancementioning
confidence: 99%